Gender, HIV/AIDS and rural livelihoods: Micro-level investigations in three Afrian countries - John Curry; Esther Wiegers; Alessandra Garbero; Shannon Stokes; John Hourihan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
HIV/AIDS has a severe impact on food security, affecting all of its dimensions: availability, stability, access, utilization. FAO recognizes that HIV/AIDS is a determining factor for, as well as a consequence of, food insecurity. Although the relationships among gender, food security and rural livelihoods have been acknowledged in the growing literature on HIV/AIDS impacts, relatively few studies provide adequate focus and empirical evidence on the gender aspects of these interrelationships among vulnerable rural households. Such gender aspects of these relationships have been explored in detail by FAO in Namibia, Uganda and Zambia This paper presents the main findings of the four baseline studies and discusses the methodologies used to identify vulnerable households and document changes in resource availability, household labour force, livelihood strategies, coping strategies and food security status. These findings offer useful insights for policy formulation purposes and for the development of mitigation strategies that respond to the food security challenges of the epidemic. – gender ; HIV/AIDS impacts ; livelihoods ; Sub-Saharan Africa
Keywords: D1; D13; J16; R2; R20; 330; AIDS; Nahrungsmittelversorgung; Lebensstandard; Landbevölkerung; Afrika; Namibia; Uganda; Sambia